Synthesis of new 2,5-disubstituted-1,3,4-thiadiazoles and preliminary evaluation of anticonvulsant and antimicrobial activities - ŞENER, GÖKSEL (My University, 2002)
Two new series of 2,5-disubstituted-1,3,4-thiadiazoles were synthesized for their possible anticonvulsant, antibacterial and antifungal activities. The degree of protection afforded by these compounds at a dose of 100mg/kg i.p. against pentylenetetrazole-induced convulsions in mice ranged from 0 to 90%. Among these compounds, 2a (90%) and 2g (70%) showed maximum protection. Antimicrobial tests showed that the MIC value of 3j against Pseudomanas aeruginosa was equal to that of penicillin.
Keywords: Animals; Pseudomonas aeruginosa; Drug Evaluation, Preclinical; Anti-Bacterial Agents; Microbial Sensitivity Tests; Mice; Mice, Inbred BALB C; Anticonvulsants; Thiadiazoles; Seizures